Educational Exercise William Flexion Exercise To Reduce Lower Back Pain - Wanti Hasmar; Adi Saputra Junaidi (Asian Journal of Community Services, 2022)
LBP is a musculoskeletal and neuromuscular condition that affects the adult population. LBP can also be caused by poor body activity or due to activities in the wrong position, while the cause is an error in sitting position when carrying out daily activities statically and for a long time. Symptoms of NBP are pain, joints that feel stiff or difficult to move and a sense of tension. Pain and spasm can cause impaired functional activity and decreased productivity at work. Community service activities were carried out on October 20-19 by distributing leaflets about low back pain . This PKM aims to reduce lower back pain with william flexion exercise Good evaluation results through questions and answers and demonstrations of the william flexion exercise